The Paradox of Leadership Coaching in a VUCA World - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2023)
What does it feel like to be living right in the middle of a major paradox? Disorienting? Confusing? Unbalancing? One of the definitions of a Paradox is a situation, person, or thing that combines contradictory features or qualities. For many organizational leaders today dealing with paradox has become a recurrent feature of executive life. The contradictory features may arise in the form of a choice between apparently diametrically opposed alternatives. In fact, in the worst case, the best available options might all be equally undesirable. This uncertainty over paradox seems to be reflective of the many quandaries confronted by leaders in the current era. Paradox often takes the form of how to best deal with the outwardly apparent oppositional answers to challenging organizational issues. Among these paradoxical questions are: How can leaders not only survive in tumultuous times but also thrive well into the future? And, what can leadership coaches, who work with these perplexed leaders, do to help them better understand and handle all the ambiguity and confusion that surrounds them on a daily basis? This paper will address these questions as well as offering a perspective for understanding the complex leadership quandary that many leaders now find themselves in. Additionally, positive recommendations will be provided for dealing with this difficult and challenging dilemma. Beginning with a discussion of the new term VUCA, the paper will discuss its origins and what leaders and coaches need to know about it. Next, the work will look at the threats and opportunities VUCA poses. This will be followed by sections on how VUCA might affect the leader-coach relationship and special considerations for coaches. The paper will conclude with specific guidance for coaches and a wrap-up summary.